Solvents Influence 1H NMR Chemical Shifts and Complete 1H and 13C NMR Spectral Assignments for Florfenicol - Ai, Wan-Ting; Su, Wei-Ke; Su, Feng (Pharmaceutical Fronts, 2023)
Florfenicol (FFC) is an important and widely used veterinary drug, and its structure has been characterized by nuclear magnetic resonance (NMR) spectroscopy. The study aimed to investigate the influences of solvent type, solvent concentration, and temperature on the chemical shifts of the 1H NMR of FFC. The results showed that different types of solvents significantly affected the chemical shifts, especially the chemical shifts of 2-H, 3-H, 5-H, and the active protons. When DMSO-d6 is used as the solvent, there is no significant difference in the chemical shifts of FFC with a concentration ranging from 20 to 250 mmol/L; however, as the temperature increases, the chemical shifts of the active protons move to a higher field. Besides, the NMR spectroscopic data and structural analysis of FFC were refined by 1H, 13C, distortionless enhancement by polarization transfer-135 (DEPT-135), 1H–1H correlation spectroscopy (1H–1H COSY), phase-sensitive gradient heteronuclear singular quantum correlation (gHSQC), and heteronuclear multiple bond correlation (gHMBC) NMR spectroscopy using DMSO-d6 as a solvent. The study will help with qualitative and quantitative analysis of FFC in the future.
Keywords: florfenicol; nuclear magnetic resonance; solvents; solvent concentrations; chemical shifts